Electroacoustic music by Georg Friedrich Haas: notes on time-space organization - Chornyi, Oleksandr (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
The relevance of the article is to consider electroacoustic music of Austrian composer Georg Friedrich Haas revealing the specifics of the composer’s work with processed acoustic and synthetic sound. The article analyzes composer’s methods of working with electronics and its interaction with acoustic instruments and performance strategies. Main objective of the study is to reveal the organization of time-space in the electroacoustic works of Georg Friedrich Haas on the examples of the works “Schattenspiel” for piano and electronics (2004) and “...und...” for chamber ensemble and live electronics (2008), by exploring the principles of Haas’s work with electroacoustic material. The scientific novelty of the article lies in the disclosure of composer’s methods and performance strategies in the interaction of acoustic and synthetic sound sources, which have not been sufficiently represented in Ukrainian musicology. The research methodology includes the methods of comparative, structural and functional analysis to study the composer’s work and his place in contemporary instrumental and electroacoustic music, content analysis to study specific markers of Haas’s composition technique and their implementation in practice, and the method of generalization to model the processes occurring in the integral system of each work. Results and conclusions. The study explores Haas’s principles of microtonal organization in both the acoustic and electronic parts, as well as the technological aspects of electronic sound production. It provides a detailed examination of the compositional techniques in “Schattenspiel” for piano and live electronics, particularly the juxtaposition of electronic and acoustic parts and the temporal-spatial effects of synchronizing the live performer with their "shadow." The analysis of “…und…” focuses on the fundamental tones and their function within the work, the role of overtone series in piece’s structure. Furthermore, the study characterizes electronic sound as an independent entity and addresses the composer’s objectives in achieving the organic integration of electronic sound. The author presents Haas’ reflections on electronic sound and compares Haas’s aesthetic paradigm with those of avant-garde composers. The cognitive aspect of human perception of different overtone series is also considered, including phenomena such as micro effects and the sound illusion caused by Shepard tones. Finally, the study outlines prospects for further research on the interaction between "live" and "non-live" materials in electronic elements, as well as the study of new performance strategies and psychoacoustic factors of listening perception